Correlation Between Copeptin and PSI with Intravenous to Oral Antibiotic Switch Theraphy and Length of Stay in Community-Acquired Pneumonia - Risky Irawan; Reviono Reviono; Harsini Harsini (Jurnal Respirologi Indonesia, 2019)
Background: Pneumonia is a world’s health problem. AVP level in the circulation is difficult to measure therefore copeptin is chosen since it is more comparable in number and more stable. Method: Prospective observational study on 25 patients with community-acquired pneumonia in Dr.Moewardi Hospital from July-August 2017. Result: There were no significant differences between switch therapy duration and length of stay to subject’s characteristic. There was a positive and significant correlation of PSI score to switch therapy and length of stay with a medium to strong correlation strength. Copeptin to switch therapy and length of stay had a positive and significant correlation with a medium to strong correlation strength. Pneumonia patients with PSI Score >90 had a risk of 36.67 times higher with switch therapy duration >4 days and it could be used as a predictor of switch therapy duration. Copeptin >17.23 with switch theraphy duration >4 days on pneumonia patient had a risk of 24.75 times higher and it could be used as a predictor of switch therapy duration. Pneumonia’s patient with PSI Score >100 with length of stay >10 days had a risk of 26.00 times higher and it could be used as a predictor of length of stay. Copeptin >27.39 with length of stay >10 days on pneumonia’s patient had a risk of 36.00 times higher and it could be used as a predictor of length of stay. Conclusion: Both PSI Score and copeptin level had positive and significant correlation to switch theraphy and length of stay. (J Respir Indo 2019; 39(1): 44-53)